Immunotoxicity of Per- and Polyfluoroalkyl Substances: Insights into Short-Chain PFAS Exposure - Woodlief, Tracey (Toxics, 2021)
Novel per- and polyfluoroalkyl substances (PFAS) were recently identified in drinking water sources throughout North Carolina. These include the perfluoroether acids (PFEAs) perfluoro-2-methoxyacetic acid (PFMOAA), perfluoro-2-methoxypropanoic acid (PFMOPrA), and perfluoro-4-methoxybutanioc acid (PFMOBA). Little toxicological data exist for these PFEAs. Therefore, the present study described signs of toxicity and immunotoxicity following oral exposure. Adult male and female C57BL/6 mice were exposed once/day for 30 days to PFMOAA (0, 0.00025, 0.025, or 2.5 mg/kg), PFMOPrA, or PFMOBA (0, 0.5, 5, or 50 mg/kg). A dose of 7.5 mg/kg of perfluorooctanoic acid (PFOA) was used as a positive control. Terminal body weights, and absolute liver, spleen, or thymus weights did not differ by dose for any compound; exposure to 50 mg/kg of PFMOBA increased relative liver weights in males. Changes in splenic cellularity were observed in males exposed to PFMOPrA and decreased numbers of B and natural killer (NK) cells were observed in males and females exposed to PFMOBA. Exposure did not alter NK cell cytotoxicity or T cell-dependent antibody responses at doses administered. Our results indicate that these “understudied” PFAS have toxicological potential but require additional investigation across endpoints and species, including humans, to understand health effects via drinking water exposure.